The Application of Inserted Steel Pipe as an Alternative Confinement Design in Reinforced Concrete Column Plastic Hinge Regions - Sudjati, Johanes Januar; Satyarno, Iman; Triwiyono, Andreas; Supriyadi, Bambang; Setiawan, Angga Fajar (Springer, 2022)
Plastic hinges in the base of columns cannot be avoided in the seismic ductile design of reinforced concrete structures. Therefore, the adequate amount of transverse reinforcement must be provided in the base of column plastic hinge regions to achieve a ductile failure mechanism. There are two objectives of providing an adequate amount of transverse reinforcement in the column plastic hinge regions. Firstly, is to prevent the shear failure mechanism and secondly is to provide adequate confinement, especially if the axial load in the columns is high. In some cases, the need for transverse reinforcement amounts is very high that makes them difficult to construct. To reduce the difficulty in constructing the transverse reinforcement, 90° hook steel bars are also used. It is known that these 90° hook steel bars are not so effective for confinement, make more congestion, and there are ineffective steel bars volumes for the hooks. This paper discusses an alternative method of conventional transverse reinforcement (CTR) to provide confinement in the column plastic hinge regions by inserting steel pipe in plastic hinge regions to reduce the amount of transverse reinforcement (CTRSP). The moment–curvature relationships and the interaction diagram for CTR and CTRSP were compared numerically. The result showed that the inserted steel pipe reduced the moment capacity deterioration significantly and increased the ductility of the column so that CTRSP was more effective for confinement than CTR. Moreover, less steel material was needed by CTRSP than CTR as no ineffective steel bars for the hooks were needed in CTRSP. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.